Immunogenicity of a Live-Attenuated Dengue Vaccine Using a Heterologous Prime-Boost Strategy in a Phase 1 Randomized Clinical Trial. (23rd September 2020) - Lin, Leyi; Koren, Michael A; Paolino, Kristopher M; Eckels, Kenneth H; De La Barrera, Rafael; Friberg, Heather; Currier, Jeffrey R; Gromowski, Gregory D; Aronson, Naomi E; Keiser, Paul B; Sklar, Marvin J; Sondergaard, Erica L; et al.
Abstract: Background: Dengue is a global health problem and the development of a tetravalent dengue vaccine with durable protection is a high priority. A heterologous prime-boost strategy has the advantage of eliciting immune responses through different mechanisms and therefore may be superior to homologous prime-boost strategies for generating durable tetravalent immunity. Methods: In this phase 1 first-in-human heterologous prime-boost study, 80 volunteers were assigned to 4 groups and received a tetravalent dengue virus (DENV-1–4) purified inactivated vaccine (TDENV-PIV) with alum adjuvant and a tetravalent dengue virus (DENV-1–4) live attenuated vaccine (TDENV-LAV) in different orders and dosing schedules (28 or 180 days apart). Results: All vaccination regimens had acceptable safety profiles and there were no vaccine-related serious adverse events. TDEN-PIV followed by TDEN-LAV induced higher neutralizing antibody titers and a higher rate of tetravalent seroconversions compared to TDEN-LAV followed by TDEN-PIV. Both TDEN-PIV followed by TDEN-LAV groups demonstrated 100% tetravalent seroconversion 28 days following the booster dose, which was maintained for most of these subjects through the day 180 measurement. Conclusions: A heterologous prime-boost vaccination strategy for dengue merits additional evaluation for safety, immunogenicity, and potential for clinical benefit. Clinical Trials Registration: NCT02239614. Abstract : A heterologous prime-boost vaccination strategy using an inactivated followed by a live-attenuated dengue vaccine demonstrated acceptable safety and produced tetravalent, durable neutralizing antibody titers.